Answer:
x = 6
Explanation:
Solve for x:
-(7 x)/3 + 14 = 0
Put each term in -(7 x)/3 + 14 over the common denominator 3: -(7 x)/3 + 14 = -(7 x)/3 + 42/3:
(-(7 x)/3 + 42/3) = 0
-(7 x)/3 + 42/3 = (-7 x + 42)/3:
((-7 x + 42)/3) = 0
Multiply both sides of (-7 x + 42)/3 = 0 by 3:
(3 (-7 x + 42))/3 = 3×0
(3 (-7 x + 42))/3 = 3/3×(-7 x + 42) = -7 x + 42:
(-7 x + 42) = 3×0
0×3 = 0:
-7 x + 42 = 0
Subtract 42 from both sides:
(42 - 42) - 7 x = -42
42 - 42 = 0:
-7 x = -42
Divide both sides of -7 x = -42 by -7:
(-7 x)/(-7) = (-42)/(-7)
(-7)/(-7) = 1:
x = (-42)/(-7)
The gcd of 42 and -7 is 7, so (-42)/(-7) = (-(7×6))/(7 (-1)) = 7/7×(-6)/(-1) = (-6)/(-1):
x = (-6)/(-1)
(-6)/(-1) = (-1)/(-1)×6 = 6:
Answer: x = 6